Egyptian Financial Supervisory Authority (EFSA) Decision No. 109 of the Year 2014 Dated 4/8/2014 On Amending Some Provisions of the Decision of the Authority’s Board of Directors No. 72 of the Year 2013 Regarding the Regulatory and Supervisory Controls Governing Factoring Activity = الهيئة العامة للرقابة المالية قرار رقم 109 لسنة 2014 بتاريخ 4/8/2014 بتعديل بعض أحكام قرار مجلس إدارة الهيئة رقم 72 لسنة 2013 بشأن الضوابط التنظيمية والرقابية لنشاط التخصيم - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic